Oona living in the shadows ; a biography of Oona O'Neill Chaplin - Scovell, Jane (Warner Books, 1998)
Oona Chaplin, the daughter of playwright Eugene O'Neill had two brothers who committed suicide at an early age and a husband, Charlie Chaplin, who was thirty-six years older than she.
Keywords: Chaplin, Charlie <1889-1977>; Chaplin, Oona; Chaplin, Oona -- 1925-1991; Comedians -- United States -- Biography; Entertainers' spouses -- Biography; Motion picture actors and actresses -- United States -- Biography; USA; Biografie